MANFAAT AVERRHOA CARAMBOLA DALAM MENURUNKAN HIPERTENSI - Jenita Doli Tine Donsu (Jurnal Penelitian Kesehatan SUARA FORIKES, 2018)
MANFAAT AVERRHOA CARAMBOLA DALAM MENURUNKAN HIPERTENSI Jenita Doli Tine Donsu*), Harmilah**), Maria H. Bakri***) *) **)***)Health Polytechnic of Health Ministry Yogyakarta Jl. Tata Bumi No. 03 Banyuraden, Gamping, Sleman, Yogyakarta Email: donsu.tine@gmail.com ABSTRACT Hypertension is a common health problem in the community. Uncontrolled hypertension can lead to degenerative diseases, such as congestive heart failure, kidney failure, and vascular disease. Hypertension is called the "silent killer" because it is symptomatic that cause strokes and heart disease. Therefore, patients with hypertension should have adherence to effectively control and obtain regular double intervention either farmako and other alternatives such as complementary therapies. The purpose of this study was to determine the star fruit (Averrhoa carambola) as a complementary therapy is effective in reducing systolic and diastolic blood pressure in patients with essential hypertension. This study begins with empirical studies and phytochemical test on star fruit in a laboratory Pharmacy Polytechnic Bandung, and worthy of ethics and the MoU between the Ministry of Health Polytechnic Yogyakarta and Bandung. This research method using experimental design, the type of Quasi experimental, with "Pre-test and Post-test Control Group Design without" 80 respondents in Community Health Centre Sleman Yogyakarta and Sukajadi Bandung. The results of the analysis of different test by Mann-Whitney that there was no significant difference to the decrease in blood pressure between the groups and slices of star fruit juice in systolic blood pressure p = 0.197 (> 0.05) and diastolic p = 0.061 (> 0.05). Results Wilcoxcon analysis, significantly there is a decrease in systolic blood pressure p = 0.000 (